1991
DOI: 10.1121/1.401906
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain analysis of the energy exchange between structural vibrations and acoustic radiation using near-field acoustical holography measurements

Abstract: The vibrational energy in a structure and the radiated acoustic energy are analyzed in the time domain using data from near-field acoustical holography measurements. A signal processing method is described that uses data from a single broadband acoustical holography measurement to determine the structural and acoustic responses for synthetic forces different from the original measurement force. The processing is based on the assumption that the measured acoustic pressure and particle velocity are related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The field quantity y{t, x, xg) (acoustic pressure or particle velocity at position x in the fluid due to the force at ZQ on the structure) can be related to the drive force by the transfer function h{T,x,XQ), which is also referred to as the impulse response function. Note that h{T,x,XQ) only relates the drive force at xq to a particular field point x; thus /i(t, X, sq) is needed for every spatial location of interest [13].…”
Section: Time Domain Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The field quantity y{t, x, xg) (acoustic pressure or particle velocity at position x in the fluid due to the force at ZQ on the structure) can be related to the drive force by the transfer function h{T,x,XQ), which is also referred to as the impulse response function. Note that h{T,x,XQ) only relates the drive force at xq to a particular field point x; thus /i(t, X, sq) is needed for every spatial location of interest [13].…”
Section: Time Domain Analysismentioning
confidence: 99%
“…It can be concluded that analyzing wave propagation and sound radiation in the time domain provides a powerful means to identify and understand phenomena. For example, the speed at which waves propagate in a structure can be determined [14], and the sound radiation resulting from a particular incident wave on a discontinuity can be seen and quantified [13]. Also the influence of different forcing functions on the response of a structure can be studied [13].…”
Section: Y{u X Xq) = A(w X Xq)f{uj Xq)mentioning
confidence: 99%
See 2 more Smart Citations
“…This can be attributed to the use of direct and inverse time domain discrete Fourier transforms ͑DFTs͒ involved in the standard NAH formulation, leading to time aliasing errors in the propagated signals if the initial data are not properly padded with zeros. 7 Aliasing errors are negligible for sound pressure signals much shorter than the observation time window. The sound pressure radiated by the loudspeakers or the transducer mentioned above are examples of very short signals.…”
Section: Introductionmentioning
confidence: 98%